Issues and challenges in implementing the wakalah-waqf model in Malaysian takaful business - Salleh, Safinar; Zahraa, Mahdi (Nova Science Publishers, 2026)
The wakalah-waqf model has been implemented in takaful business operations to address several Shariah issues emerging from the lack of a legal entity for the takaful fund (risk fund) under both mudarabah and wakalah models. The two models do not specify the owners of the contributions to the takaful fund, and the fund does not belong to takaful operators or takaful participants as takaful participants have paid the takaful contributions as donations (tabarru’). Certain researchers embrace the perspective that the takaful fund is the owner of all contributions, profits generated from investments, and surplus in the fund after deducting claims and expenditures. Accordingly, the fund should be developed as a waqf fund with a legal entity. The current study seeks to examine the appropriateness of the wakalah-waqf model for takaful business operations by appraising compliance with Shariah principles and discussing several issues and challenges in implementing the takaful model in Malaysia with potential solutions. This study is academic legal research encompassing doctrinal analysis and a comprehensive review of primary and secondary data from relevant statutes, Islamic legal texts, takaful documents, waqf deeds, academic journals, and publications. The results demonstrated establishing a takaful fund based on waqf could address several Shariah issues due to the implementation of the other operational models despite certain limitations to be resolved via separate approaches or modifications for further improvements.